(untitled) (Research, Society and Development, 2021)
Menopause is a biological process that happens in women, since the ovaries stop producing hormones due to the lack of eggs. This stage of a women’s life can happen at 35 to 60 years, and might cause uncomfortable symptoms and even diseases, worsening the life quality of women. The cessation of ovulation has the consequence of reducing the production of estradiol that causes a change in the immune system, predisposing to inflammatory and infectious diseases. Such predisposition can increase the inflammatory mediators IL-6 and IL-17 in the female organism. Melatonin is a hormone manufactured by the pineal gland at night, since the light can debug the hormone. This hormone regulates the circadian rhythm and an immunomodulator. This immunomodulating function that melatonin has can mediate the synthesis and inhibition of some inflammatory mediators. This review aims to identify if melatonin treatment can reduce the quantity of inflammatory mediators in menopausal women. This analysis was performed through a review, with papers searched in the PubMed, Scielo, ScienceDirect and RBAC databases using the keywords: melatonin, menopause, inflammatory mediator, inflammatory modulation, published in the last 15 years. Analyzing the articles, it was identified that melatonin influences the decrease of inflammatory mediators, which may help to improve the life quality of women that are or will be in menopause. However, it is necessary to search for protocols for the use of melatonin, with prediction of use doses and verification of the effects on the body.